Treatment of Cellulose Bleaching Effluents and Their Filtration Permeates by Anodic Oxidation with H2o2 Production - Salazar-Gonzalez, R (John Wiley and Sons Ltd, 2015)
BACKGROUND: Electrochemical advanced oxidation processes (EAOPs), particularly those based on either cathodic electrogeneration of H2O2 or anodic oxidation (AO) via •OH, have become attractive technological options for the complete detoxification of wastewaters. Their integration with separation pre-treatment such as ultrafiltration (UF), nanofiltration (NF) or reverse osmosis (RO) may be a plausible way to reduce processing time and costs. RESULTS: Raw effluents from the acid and alkaline elemental chlorine free bleaching stages of a hardwood-based kraft pulp mill, as well as their UF, NF and RO permeates, have been characterized and then treated by AO-H2O2 in a tank reactor with an air-diffusion cathode, which allowed efficient reduction of O2, and a DSA-RuO2 or BDD anode at constant cell voltage (2-12V). Due to the complexity of the matrix, a larger H2O2 accumulation in the acid effluents was observed. DSA favoured the accumulation of ClO2- ions, whereas BDD allowed their further transformation into ClO3- owing to the larger oxidizing power of its physisorbed •OH. The contribution of this species, along with H2O2 and active chlorine, accounted for the significant TOC abatement reached in the different individual and coupled treatments. CONCLUSIONS: AO-H2O2 and UF/AO-H2O2 yielded similar mineralization levels (65-68%) for acid effluents, but lower energy consumption (EC) resulted in the latter process due to the lower conductivity of the permeates. NF/AO-H2O2 coupling yielded the largest mineralization of alkaline effluents (96% instead of 75% obtained by AO-H2O2) with low EC. © 2015 Society of Chemical Industry.